Physico-Chemical Properties of Bread Made of Frozen Dough Incorporated with Rubber Seed ( Hevea Brasiliensis) Flour Stored at Different Storage Temperature - Asyikeen Zulkifli, Noroul; Syahirah Zulkefli, Nadia; Lee Hoon, Ho; Abd. Ghani, Maaruf (International Journal of Engineering and Technology, 2018)
Rubber seed is an underutilised by-product from rubber seeds and contains high protein. The dough that undergoes freezing negatively affects the quality of the end product. This study was conducted to determine the physical and chemical properties of bread that was made from frozen dough, incorporated with rubber seed flour (RSF) and stored at different storage temperatures. The formulation varied from control 100% bread flour, 100% RSF and bread dough prepared from substituted RSF with percentages of 25%, 50% and 75%. The dough was stored at temperatures of 25 Â°C, 10 Â°C, 4 Â°C and âˆ’18 Â°C for 14 days. Straight dough method was used to make the bread. Analyses were conducted on specific volume, texture, moisture content, water activity, porosity and pH. Results showed that bread formulated with RSF had low moisture content and water activity. However, the specific volume was high in the bread with different formulation and storage temperature. Among the formulation RSF25 showed the most suitable formulation to be used for frozen dough with the specific volume of 5.44Â±0.007 cm3/g, when stored at lower temperature (-18 Â°C). Â The bread made of rubber seeds showed significant difference in texture, pore size and pH. In conclusion, the use of RSF can improve the quality of the bread made from frozen dough.Â Â